STRENGTHENING ONE HEALTH IMPLEMENTATION AT AIRPORTS THROUGH CROSS-SECTORAL BIOSECURITY MANAGEMENT - Dian Ayu Permatasari; Dadik Raharjo; Mustofa Helmi Effendi; Budiarto; Lucia Tri Suwanti (Jurnal Layanan Masyarakat (Journal of Public Services), 2026)
This community service program was directed at enhancing the implementation of the One Health approach at airports through cross-sectoral biosecurity management. Airports are important gateways where close interactions among humans, animals and the environment create a high potential for the emergence of zoonotic diseases. The activities were conducted at Sultan Hasanuddin International Airport and involved airport authorites, airport operational staff, quarantine officers, public health agencies, and academic collaborators. The program include socialization sessions, focus group discussions, workshops, and mentoring activities aimed at  strengthening stakeholders understanding of One Health principles and improving coordination mechanisms in biosecurity management. The results indicated improved cross-sectoral coordination, increased awareness of zoonotic risks management, and greater preparedness among participants to implement standardized biosecurity practices. The academic capacity building activities supported participants readiness for scientific publication and improved citation strategies. Overall, the program demonstrates that a cross-sectoral biosecurity management approach can serve as an effective strategy to strengthens the implementation of One Health at airports and promote sustainable public health protection.